On the different origins of electrical parameter degradation in reverse‐bias stressed AlGaN/GaN HEMTs. Issue 6 (3rd February 2016) - Ghosh, Saptarsi; Dinara, Syed M.; Mahata, Mihir; Das, Subhashis; Mukhopadhyay, Partha; Jana, Sanjay Kumar; Biswas, Dhrubes
Abstract : Reverse bias stressing in AlGaN/GaN high electron mobility transistors (HEMTs) compelled severe degradation of drain current ( I DS ) whereas gate current ( I G ) remained largely unaffected. Besides, the response of access region conductivity to pulse drives was found to deteriorate gradually as a result of stress, and an interacting deep level in the form of kink effect was observed. Post degradation, SEM imaging evidenced the field‐induced formation of protruding particles, immediately adjacent to the gate electrode. Auger spectroscopy and elemental mapping chemically identified these insulating particles as gallium oxide. Barrier/channel consumption in the form of electrochemical oxidation is thus held responsible for I DS degradation whereas I G degradation is entirely attributed on the presence of passivation layer. SEM micrographs of the (a) tested, and (b) untested finger of a −80 V bias stressed HEMT. (c) Auger spectra from an insulating particle, whereas (d) and (e) are oxygen and gallium elemental maps of the entire frame (c).